Analysis of the Effectiveness of the Contextual Teaching and Learning (CTL) Model in the Teaching of the Qur'an and Hadith to Eleventh Grade Students at MA Azzanjabil Buket Teukuh in Bireuen Regency - Tasya Ananda Putri; Nia Wardhani; Yusnaini; Zalifah Saura (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the application of the Contextual Teaching and Learning (CTL) model in the Al-Qur'an Hadith subject in class XI MAS Azzanjabil. Teachers act as facilitators who guide students to explore the contents of verses and hadiths, then relate them to the values that develop in society. The activities consist of six main components: (1) Constructivism, where students build knowledge through experience. (2) Inquiry, learning through the process of asking questions and discovering. (3) Questioning, where teachers and students actively ask questions to explore knowledge. (4) Learning community, where cooperation among students in groups is created. (5) Modeling, where teachers provide concrete examples of what is being learned. (6) Reflection, where students reflect on the learning process and outcomes. All these methods enable students to actively engage in collaborative and contextual learning. This study used a qualitative analysis research approach with data collection techniques in the form of observation, interviews, and documentation of Al-Qur'an Hadith teachers. The results of the study showed significant results. Students experienced an increase in their understanding of the material. Students were able to explain concepts from the Qur'an and Hadith using everyday language, indicating that they not only memorized the material but also understood it deeply. In addition, students were active in group discussions and were able to ask relevant questions. The practical application of this learning method can be seen when students perform the Dhuha prayer at the school mosque, perform the five daily prayers in congregation, respect teachers by greeting them when passing by, and greet teachers, which shows that students are able to apply the knowledge they have acquired in their daily lives. The evaluation results show that the majority of students achieved better scores compared to the previous conventional learning method.